2004
DOI: 10.1207/s15327752jpa8303_12
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Symptom Change in Treatment-Refractory Inpatients: Evaluation of the Phase Model of Change Using Rorschach, TAT, and DSM-IV Axis V

Abstract: In this study, we examined global treatment outcomes during 16 months of intensive, psychodynamic treatment for 77 inpatients suffering from treatment-refractory disorders. Hypotheses based on the phase model of treatment change (Howard, Lueger, Maling, & Martinovich, 1993; Howard, Moras, Brill, Martinovich, & Lutz, 1996) were supported in the study results. Diagnostic and Statistical Manual of Mental Disorders (4th ed.; American Psychiatric Association, 1994) Axis V scales assessing behavioral functioning dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 74 publications
4
63
2
6
Order By: Relevance
“…The majority of previous research regarding the phase model indicates that the progression through the stages follows a largely invariant sequence (Fowler et al, 2004;Schwartz, 1997). These findings are in contrast to the current ones which indicate that rehabilitation appears to occur simultaneously with remediation, thus casting doubt on the invariance of the phases, as well as the notion that each successive phase cannot start without the previous one concluding.…”
Section: Co-occuring Phases and The Phase Modelcontrasting
confidence: 90%
“…The majority of previous research regarding the phase model indicates that the progression through the stages follows a largely invariant sequence (Fowler et al, 2004;Schwartz, 1997). These findings are in contrast to the current ones which indicate that rehabilitation appears to occur simultaneously with remediation, thus casting doubt on the invariance of the phases, as well as the notion that each successive phase cannot start without the previous one concluding.…”
Section: Co-occuring Phases and The Phase Modelcontrasting
confidence: 90%
“…Additionally, we were not able to use two of the SCORS variables (e.g., EIM and ICS) in the present study due to poor reliability. While the SCORS has been repeatedly shown to be a reliable measure (Eudell-Simmons, Stein, DeFife, & Hilsenroth, 2005;Fowler, Hilsenroth, & Handler, 1995;Fowler et al, 2004;Porcerelli, Cogan, & Hibbard, 1998;Stein et al, 2007), reliability for these two variables were questionable in the present study and thus unavailable for use. This is particularly unfortunate with regards to EIM, which we expected would differ considerable across attachment types.…”
Section: Discussionmentioning
confidence: 62%
“…They suggest that attachment styles are 'enduring characteristics that are not easily modifi ed ' (p. 1062). Prior research with the SCORS, however, has shown sensitivity to change in internal representations (Fowler, Ackerman, Speanburg, Bailey, & Blagys, 2004;Porcerelli, Shahar, Blatt, Ford, Mezza, & Greenlee, 2006). It is possible that explicit self-report measures may be particularly useful as assessment tools of more stable personality characteristics, while narrative-based methods like the SCORS may have excellent utility for understanding change as a function of therapy over time.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant examples indicate the occurrence of positive therapeutic changes for aggression, self-esteem, emotional investment in relationships or attachment, hostility, decision making, risk taking, and drug abuse for inpatient and outpatient adults (Fowler et al, 2004;Gossop, Marsden, Stewart, & Treacy, 2002;Prendergast, Farabee, Cartier, & Henkin, 2002). It stands to reason that positive dynamic variable change through treatment is also possible for offenders, and that such change may in fact reduce rates of recidivism.…”
Section: Risk and Need Assessment Voidmentioning
confidence: 99%